Topical Impact of Nanosimvastatin on Bone Fracture - Luay H. Jalil (Dentistry 3000)
Bone healing is a vert complex process. Fracture healing is a major challenge in orthopaedic practice and research. Simvastatin is an encouraging novel bone regeneration inducer due to its safety, low cost, and clinical convenience. However, the specific mechanism of simvastatin's effect on bone growth, as well as the best dose, are unknown. Simvastatin is a biodegradable polymer that promotes bone growth. A total number of 16 adult albino rabbits were divided into two groups (8 rabbits /each). A defect was done in bone and filled with gel only for controls and treatment specimens were filled with nanoliposomal simvastatin. The results showed that the treatment group with nanosimvastatin gel had a significant improvement in bone healing compared to the control group.